Effect of nutritional intervention and dietary modification on the health status of pediatric acute lymphoblastic leukemia patients - Ghaffar, Fazia; Mehmood, Noureen; Khan, Imran; Din, Zia Ud; Iqbal, Zafar; Iqbal, Mudassar (Progress in Nutrition, 2019)
In order to ascertain the effectiveness of nutrient rich diet and dietary counseling on the health status of pediatric acute lymphoblastic leukemia patients, this experimental study was conducted at the Institute of Radiology and Nuclear Medicine, Peshawar. A sample of 30 leukemia patients were divided into experimental and control groups based on written consents. Data regarding demographic characteristics, anthropometric measurements, and retrospective food intakes were recorded on self-constructed questionnaire. Patients in the experimental group received dietary guidelines for nutrient rich diet. Anthropometry, dietary evaluation, and blood nutrients namely serum ferritin, albumin, globulin, total protein and creatinine at 30, 60 and 90 days intervals were assessed. The data showed low height for age and low weight or height at diagnosis indicating malnourishment and wasting among all the patients. After nutritional intervention mean weights of patients in the experimental group increased significantly over period of three months. Progressive weight loss was observed in patients of control group. Blood nutrients at diagnosis showed low Hb (9.19±3.11 and 9.31±1.07 g/dL) and serum ferritin (530±4.28 and 525±3.22 ng/mL) and increased total protein (7.28±3.07 and 7.67±2.76) in both groups. These indices improved in the experimental group over a period of 90 days. Nutrient intake in the experimental group patients improved significantly for all the nutrients.